2011
DOI: 10.1088/2041-8205/737/1/l17
|View full text |Cite
|
Sign up to set email alerts
|

A Synchrotron Self-Compton-Disk Reprocessing Model for Optical/X-Ray Correlation in Black Hole X-Ray Binaries

Abstract: Physical picture of the emission mechanisms operating in the X-ray binaries was put under question by the simultaneous optical/X-ray observations with high time resolution. The light curves of the two energy bands appeared to be connected and the cross-correlation functions observed in three black hole binaries exhibited a complicated shape. They show a dip of the optical emission a few seconds before the X-ray peak and the optical flare just after the X-ray peak. This behavior could not be explained in terms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 30 publications
5
100
0
Order By: Relevance
“…Data on other black hole binaries 33 is currently too insensitive to probe the fast correlation features in question here. Swift J1753.5--0127 can be well explained by synchrotron self--Compton in a hot flow 31 . Consistent with this, the source is known to be radio--quiet with no strong requirement for a jet contributing much to the optical regime 27 .…”
Section: Comparison To Other Sources With Fast Timing Datamentioning
confidence: 94%
“…Data on other black hole binaries 33 is currently too insensitive to probe the fast correlation features in question here. Swift J1753.5--0127 can be well explained by synchrotron self--Compton in a hot flow 31 . Consistent with this, the source is known to be radio--quiet with no strong requirement for a jet contributing much to the optical regime 27 .…”
Section: Comparison To Other Sources With Fast Timing Datamentioning
confidence: 94%
“…There are three possible candidates that may account for this emission: the irradiated disc (Cunningham 1976;Gierliński et al 2009), hot accretion flow (Veledina et al 2013a) and the jet (Hynes et al 2002;Gallo et al 2007). Sometimes the OIR fluxes are higher than expected from any candidate alone (Chaty et al 2003;Gandhi et al 2010), and the complex optical/X-ray cross-correlation functions ⋆ E-mail: juri.poutanen@utu.fi (Kanbach et al 2001;Durant et al 2008) support this anticipation, suggesting contribution of two components simultaneously (Veledina, Poutanen, & Vurm 2011b). The source of OIR emission cannot be determined by only using photometric data and some additional information about the OIR-X-ray connection, short time-scale variability properties and the long-term spectral variations is required (see review in Poutanen & Veledina 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the spectral model also predicts the connection between the OIR and the X-ray aperiodic variability. However, simultaneous analysis of light curves in these wavelengths (Motch et al 1983;Kanbach et al 2001;Hynes et al 2003;Durant et al 2008;Gandhi et al 2010) has revealed a complicated connection between them, which can be understood if one considers several components contributing to the optical (Veledina et al 2011), namely the hot accretion flow and the reprocessed radiation. Additionally, the jet optically thin synchrotron emission can also be significant (e.g., Casella et al 2010).…”
Section: Introductionmentioning
confidence: 99%